Dahlia Tuber Extract and Bacillus subtilis Encapsulation in the Ration of Broiler Chickens: Combined Effects on Blood Fat Profile and Live Weight - Mulyono Mulyono; Istna Mangisah; Lilik Krismiyanto; Vitus Dwi Yunianto; Wafiq Afifah Maulidyah (Research Perspective on Biological Science Vol. 4, 2025)
Background: Antibiotic Growth Promoter (AGP) as a growth promoter has been banned in Indonesia since 2017. This has prompted the search for alternative antibiotics to support poultry products’ health, productivity, and safety. This makes probiotics, prebiotics, and synbiotics potential alternatives to replace AGP. Aim of the Study: This study aims to test the effect of adding encapsulated dahlia tuber extract as a prebiotic and Bacillus subtilis as a probiotic on blood lipid profiles and live weight of broiler chicken. Methodology: The research was conducted from October to December 2023, at the Poultry Cage and the Laboratory of Nutrition and Feed Science, Faculty of Animal and Agricultural Sciences, Diponegoro University, Semarang, Indonesia. In this investigation, 200 unsexed Ross strain broilers aged 8 days with an average body weight of 194.53 ± 3.46 g were used. The treatment feed was administered at the age of 8-35 days, containing encapsulated dahlia tuber extract as a prebiotic and Bacillus subtilis as a probiotic (EDTEBs). Dahlia tuber extract and Bacillus subtilis were mixed in a 50:50 ratio. The study used a completely randomised design (CRD) with 4 treatments and 5 replications, each consisting of 10 broilers. The treatment given was T0: basal ration, T1: basal ration + 0.1% EDTEBs, T2: basal ration + 0.2% EDTEBs, T3: basal ration + 0.3% EDTEBs. The parameters measured were blood cholesterol, triglyceride, high-density lipoprotein (HDL), low-density lipoprotein (LDL) levels, and live weight. Data were analysed using the JASP program. Results: The results showed that the addition of dahlia tuber extract encapsulation and Bacillus subtilis encapsulation had a significant effect on cholesterol levels (P < 0.001), triglycerides (P<0.001), HDL (P = 0.002), LDL (P = 0.001), and live weight (P < 0.001) in broilers. The addition of EDTEBs at a concentration of 0.1% yielded optimal results in reducing cholesterol, triglycerides, and LDL levels, while also increasing HDL levels and live weight in broilers. Conclusion: The effectiveness of the combination of Dahlia tuber extract and Bacillus subtilis can be reduced in the digestive tract, as the bioactive compounds and probiotic bacteria may be damaged by acidic gastrointestinal conditions. The addition of encapsulated dahlia tuber extract and Bacillus subtilis at a 0.1% level improved the blood lipid profile of broiler chickens by reducing cholesterol, triglyceride, and LDL levels while increasing HDL levels and live weight. The best results were obtained in the 3% addition treatment.